2020
DOI: 10.3390/mps3030052
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Radiographic Evaluation of the Malar Bone Engagement Available for Ideal Zygomatic Implant Placement

Abstract: Zygomatic implant rehabilitation is a challenging procedure that requires an accurate prosthetic and implant plan. The aim of this study was to evaluate the malar bone available for three-dimensional zygomatic implant placement on the possible trajectories exhibiting optimal occlusal emergence. After a preliminary analysis on 30 computed tomography (CT) scans of dentate patients to identify the ideal implant emergencies, we used 80 CT scans of edentulous patients to create two sagittal planes representing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
(46 reference statements)
0
11
0
2
Order By: Relevance
“…Impressions obtained with conventional materials (polyether and polyvinylsiloxane) are the most common procedures in clinical practice; conventional workflows and CAD/CAM technologies can be combined through indirect digitalization [ 20 ]. However, new digital techniques allow the full digitalization of the workflow—intraoral digital scanners, through direct scanning, can create a virtual 3D model [ 21 , 22 ]. The main feature to be evaluated in an intraoral scanner is accuracy, which is the result of the analysis of trueness and precision [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impressions obtained with conventional materials (polyether and polyvinylsiloxane) are the most common procedures in clinical practice; conventional workflows and CAD/CAM technologies can be combined through indirect digitalization [ 20 ]. However, new digital techniques allow the full digitalization of the workflow—intraoral digital scanners, through direct scanning, can create a virtual 3D model [ 21 , 22 ]. The main feature to be evaluated in an intraoral scanner is accuracy, which is the result of the analysis of trueness and precision [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the spatial position of the affected side can be recorded in accordance with the reference to the normal side pre-and postoperatively (17) . The precision and reproducibility of these landmarks have been extremely studied by some authors, (39,40) who compared the results of the unaffected side pre-and postoperatively and they found that there was no actually difference in the radiographic points positions . Similarly in this study, the distance between the four pairs of anatomical landmarks and the three reference planes (x, y, and z) were measured pre-and postoperatively, and it was found that these landmarks can be easily marked and quantitatively assessed the degree of fracture displacement and the accuracy of ZMC reduction and fixation, as also reported by other studies (39,41) .…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, the screw-retained prosthesis on implants has become increasingly common for the rehabilitation of the totally edentulous patients [1][2][3]. Multiple solutions for the rehabilitation of upper and lower jaw were proposed and accepted in literature, basing on the entity of bone atrophy, the pneumatization of maxillary sinus, the quantity of bone available and the position of inferior alveolar nerve and mental foramina [4][5][6][7]. The All-On-Four technique for the rehabilitation of completely edentulous mandibles, initially proposed by Malo et al [8] is nowadays used by several clinicians [9][10][11] in order to reach the correct masticatory and speech functions, as well as an optimal prosthetic support, and to re-establish an acceptable situation for the patient [12].…”
Section: Introductionmentioning
confidence: 99%